Given the expression:
![x^2-2x-3=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/yo8vgmlwg7lv3u5jeu6i2sr2lpnn2bauth.png)
We will rewrite the expression to be as the form (x - a)² = b
So, we need to make a complete square
![x^2-2x=3](https://img.qammunity.org/2023/formulas/mathematics/high-school/gervr9v74g8c9ul2qysbtr41q7e7uhj68q.png)
The coefficient of x = -2
Half the coefficient = -1
Square it will give 1
So, add (1) to both sides of the equation
![x^2-2x+1=3+1](https://img.qammunity.org/2023/formulas/mathematics/high-school/a7pz3yxhfrwl5p0wk4piupq45oxo4hjczu.png)
Factor the left side of the equation, it is a complete square
![(x-1)^2=4](https://img.qammunity.org/2023/formulas/mathematics/college/pel26vxyquv02379uc4snkcoj13li52r3f.png)
Compare the result to the given form.
So, the answer will be:
![a=1,and,b=4](https://img.qammunity.org/2023/formulas/mathematics/high-school/n39kp0wjbfibr9bnf0ltcet3fpxw9dbmo5.png)